Challenges and Prospects for Replacement Money in Addressing Corruption Crimes in the Indonesian Corporate World - Hari Palar; Faisal Santiago (Journal of Social Research, 2023)
This research examines the challenges and prospects of implementing replacement money in tackling criminal acts of corruption in the Indonesian corporate world. The research method was carried out through a normative juridical approach by analyzing related laws, case studies, and interviews with legal and business practitioners. The discussion begins by exploring the legal context, especially Article 18B of Law Number 31 of 1999 concerning the Eradication of Corruption as amended by Law Number 20 of 2001. The results of the research show that the application of replacement money as a legal instrument has significant prospects in providing a deterrent effect. and recover state losses. However, challenges arise in implementation practices, especially regarding the availability of accurate financial data and the company's ability to pay replacement money. Article 18B which provides the legal basis for the application of replacement money also requires further clarification to ensure consistency and effectiveness in handling corruption cases in the corporate world. The research results show that although replacement money has prospects in overcoming criminal acts of corruption in the business sector, additional steps are needed to increase its effectiveness. Recommendations include increasing cooperation between law enforcement agencies and companies, as well as expanding the scope of regulations to cover more aspects of business practices that have the potential to become a venue for corrupt practices. This research contributes to detailing the challenges and prospects for implementing replacement money as a legal instrument in the context of criminal acts of corruption in the Indonesian corporate world.